Wound pH and autograft taking in burn wounds: An experimental study - Mostafa Dahmardehi; Ali Ahmadabadi; Majid Khadem-Rezaiyan; Farhang Safarnejad; Tayyeb Ghadimi; Hamidreza Alizadeh Otaghvar (Wolters Kluwer Medknow Publications, 2020)
Background: The appropriateness of the wound bed for autograft transplantation is routinely evaluated based on the surgeon's judgment, which might not be reliable in some situations. Therefore, this study was designed to evaluate the association between wound pH, wound temperature, and wound culture results with autograft taking. Materials and Methods: In this prospective, cross-sectional study, the body core temperature, wound pH, and local wound temperature at the beginning of operation and after burn wound excision were measured in 50 patients with burn wounds. Swab culture specimen was obtained from the burn wound after dressing removal and after the completion of wound excision. Autograft taking was evaluated on days 3 and 7 postoperative. Results: There was a statistically significant reverse association between autograft taking on day 3 and wound pH at the beginning of operation (P = 0.016). Besides, there was a statistically significant association between core body temperature and autograft taking on days 3 (P = 0.035) and 7 (P = 0.002). However, there was no significant association between local wound temperature and autograft taking. A positive result for wound culture after excision, even when the colony count was <102, was significantly associated with autograft taking on days 3 and 7. Conclusions: Wound pH measurement after dressing removal in the operation room may be a simple and available modality to evaluate the appropriateness of burn wound for skin autografting.